ASN Indiscipline in Bureaucracy: A Case Study of the Financial Sub-Sector of BPSDMD South Sumatra Province - Indah Astuti; Dwiki Adi Putra; Amaliatulwalidain (Universitas Muhammadiyah Palu, 2026)
The discipline of employees in their work is very important for the smooth performance of Civil Servants (ASN), as discipline can influence management's actions to encourage ASN employees to meet demands. In this study, the author discusses the pathology that commonly occurs in the workplace or agencies, typically carried out by certain individuals. The aim of this writing is to understand how the BPSDMD agency handles bureaucratic pathology and what actions are taken against indisciplined employees. This thesis is written using a descriptive qualitative method, collecting data sources through interviews, observation, and documentation. The results of this research find that there are still employees who are undisciplined in their work, particularly regarding obligations and attendance at the Region's Human Resources Development Agency (BPSDMD) of the Province. This research provides recommendations for further improvement in communication between employees and supervisors on a continuous basis for the implementation of discipline that is in accordance with norms, particularly discipline in duties and attendance at work, as well as providing motivation and appreciation for disciplined employees.